2018
DOI: 10.1186/s12888-018-1853-1
|View full text |Cite
|
Sign up to set email alerts
|

First-episode psychosis in treatment-resistant schizophrenia: a cross-sectional study of a long-term follow-up cohort

Abstract: BackgroundApproximately one-third of schizophrenia patients eventually develop treatment-resistant schizophrenia (TRS). Although the time course of TRS development varies from patient to patient, the details of these variations have not been clarified. The present study compared the duration of time required to achieve control of the first-episode psychosis (FEP) between patients who went on to develop TRS and those who did not, in order to determine whether a bifurcation point exists for the transition to TRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
(21 reference statements)
1
6
0
1
Order By: Relevance
“…This finding is consistent with previous studies that have identified premorbid social functioning as predictive of poor outcomes in schizophrenia and also TRP. 32 Furthermore, lower premorbid IQ (estimated from the National Adult Reading Test) was associated with an increased risk of TRP in multivariate regression analysis (odds ratio 0.98, 95% CI = 0.96–0.99) and was identified by the conditional inference forest model as predictive. These premorbid factors have been implicated in other studies of poor outcomes in schizophrenia 10,33 and warrant further investigation for their role in treatment resistance.…”
Section: Discussionmentioning
confidence: 97%
“…This finding is consistent with previous studies that have identified premorbid social functioning as predictive of poor outcomes in schizophrenia and also TRP. 32 Furthermore, lower premorbid IQ (estimated from the National Adult Reading Test) was associated with an increased risk of TRP in multivariate regression analysis (odds ratio 0.98, 95% CI = 0.96–0.99) and was identified by the conditional inference forest model as predictive. These premorbid factors have been implicated in other studies of poor outcomes in schizophrenia 10,33 and warrant further investigation for their role in treatment resistance.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, the refractory process TRS patients experience during their long-term disease course cannot be explained only by the subtle autistic traits observed in future TRS patients. However, some longitudinal studies suggested that future TRS patients could have a more difficult clinical course after their first episode of psychosis compared to that of non-TRS patients ( Demjaha et al, 2017 ; Kanahara et al, 2018 ; Lally et al, 2016 ). It is uncertain how the subtle autistic traits identified in TRS patients could affect their severe psychotic symptoms as part of the TRS etiology.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 7.4% of the patients were treated with clozapine at 2 years follow‐up. This proportion seems low considering that the rate of resistance to AP treatment among patients with schizophrenia is approximately one‐third of that among patients with FEP (Kanahara et al, 2018), and this resistance is present in a high proportion (84%) of patients from illness onset (Demjaha et al, 2017). Unfortunately, there is still a delay between the diagnosis of resistant psychosis treatment and the starting with clozapine treatment (Doyle et al, 2017; Thien and O'Donoghue, 2019).…”
Section: Discussionmentioning
confidence: 99%